Short communication: Morphological characteristics of flower and fruit in several rambutan (Nephelium lappaceum) cultivars in Serang City, Banten, Indonesia - GUT WINDARSIH; MUHAMMAD EFENDI (Society for Indonesian Biodiversity, 2019)
Abstract. Windarsih G, Efendi M. 2019. Morphological characteristics of flower and fruit in several rambutan (Nephelium lappaceum L.) cultivars in Serang City, Banten, Indonesia. Biodiversitas 20: 1442-1449. Indonesia is one of the centers of diversity of rambutan in the world with 22 species. Compared to other species, Nephelium lappaceum L. is mostly cultivated species. This study aimed to identify the generative morphological variation in several rambutan cultivars in the area of Serang City, Banten Province. The plant materials used were five cultivars of rambutan, Parakan, Rapiah, Aceh, Sinyonya, wild type, and male trees. In each plant, three bunches of inflorescence were taken, and then the flowers from each bunch were observed when the flowering phase was open (blooming). In addition, 3-5 fruit bunches were taken per plant, and then 3-5 fruits per bunch were observed. Based on the results obtained, it can be concluded that there is monoecious plants of rambutan (Aceh, Rapiah, wild type), and dioecious plant (male tree). In a monoecious plant, it produces the hermaphrodite flowers, whereas, in a dioecious plant, it just produces the male flowers. In the hermaphrodite flower, it is composed of pedicel, tepal, stamen, and pistil, while the male flower does not have pistil. The Aceh cultivar has the longest average fruit bunch (22.90 cm), Rapiah has highest number of fruit per bunch (15.86 fruits), Parakan has highest spine density (11.64 strands per 1x1 cm2) and longest spine (13.2 mm), Rapiah has a shortest average spine (3.4 mm) with a stiff texture, Rapiah and Aceh have a thickest of fruit rind (3.3 mm). Aceh has the largest size and weight of fruit with the fruit length 4.62 cm, fruit diameter 3.83 cm, fruit weight 37.42 g, weight of fruit rind 17.51 g, weight of aryl 17.94 g, and thickness of aryl 7.7 mm. From a dendrogram analysis, the five cultivars had a similarity distance coefficient from 40% to 69%. Parakan and Sinyonya had highest similarity distance (69%), while Aceh was separated from other cultivars with a similarity distance 40%.